Seizures in patients with systemic lupus erythematosus: data from LUMINA, a multiethnic cohort (LUMINA LIV) (2008)
ABSTRACT: Objective To examine the predictors of time-to-seizure occurrence and their impact on damage accrual and mortality in LUMINA, a multiethnic (Hispanic, African American and Caucasian) cohort of patients with systemic lupus erythematosus. Methods Seizures were defined as per the American College of Rheumatology (ARC) nomenclature and case definitions for neuropsychiatric lupus syndromes. Factors associated with time-to-seizure occurrence occurring at or after diagnosis (TD) of systemic lupus erythematosus were examined by univariable and multivariable Cox proportional hazard regression analyses. The impact of seizures on damage accrual and mortality was also examined by multivariable analyses after adjusting for variables known to affect these outcomes. Results A total of 600 patients were included in these analyses. Of them, 40 (6.7%) developed seizures at or after TD; by multivariable analyses, disease activity and younger age were independent predictors of a shorter time-to-seizure occurrence (HR = 1.10 and 1.04; 95% CI 1.04 to 1.15 and 1.00 to 1.08, p = 0.0004 and 0.0304, respectively) whereas mucocutaneous involvement (HR = 0.34, 95% CI 0.16 to 0.41, p = 0.0039) and hydroxychloroquine use (HR = 0.35, 95% CI 0.15 to 0.80, p = 0.0131) were independent predictors of a longer time-to-seizure occurrence. Seizures were an independent contributor to damage accrual but not to mortality. Conclusions Seizures tend to occur early in the course of systemic lupus erythematosus, and contribute to damage accrual. Younger age and disease activity are independent predictors of a shorter time-to-seizure occurrence; antimalarials appear to have a protective role in seizure occurrence. Neuropsychiatric manifestations of systemic lupus erythematosus (SLE) comprise a complex array of neurological, psychiatric and behavioural manifestations. Seizures are probably one of the most ominous and relevant clinical expressions of damage accrual in SLE,1 hence, of its long-term prognosis. Different mechanisms of nervous tissue injury have been described in SLE but a precise one is yet to be elucidated. Indeed, the secretion of pro-inflammatory cytokines (such as interleukin 1 and 6, and tumour necrosis factor-α) leads to the activation of the hypothalamic—pituitary—adrenal axis with the consequent reduction of the seizure threshold.2-4 In this setting of ongoing inflammation, anti-neuronal antibodies have been recognised in the serum of patients with SLE suffering from neurological manifestations such as encephalopathies and seizures.2 5 Focal ischaemia and/or infarcts resulting from vascular occlusion secondary to thrombosis, embolism, vasculopathy or haemorrhage are also recognised as possible causative factors of seizures in SLE.2 6 Furthermore, these patients may experience other clinical events that may increase their risk of developing seizures and the occurrence of seizures may associate with other serious clinical events. Given these evidences, we decided to examine the factors associated with time-to-seizure occurrence, as a primary manifestation of SLE, in LUMINA, a large multiethnic cohort. We hypothesised that patients with other serious disease manifestations and higher levels of disease activity will experience seizures early in the course of their disease and that seizures will contribute to damage accrual and mortality.